A secure and robust color image watermarking method using SVD and GAT in the multiresolution DCHWT domain - Boubakeur Latreche; Hilal Naimi; Slami Saadi (The Journal of Engineering and Exact Sciences)
This paper introduces an innovative and robust watermarking technique for safeguarding the copyright of color digital images. The method operates within the domain of SVD-based multiresolution discrete cosine harmonic wavelet transforms. In this approach, the pre-processing phase employs successive generalized Arnold transforms to encrypt the RGB watermark layers, significantly enhancing the security of the watermarking algorithm. Subsequently, the blue layer of the host image undergoes R-level 2D-DCHWT processing. The encrypted watermark is embedded by altering the singular values of the host image's approximation coefficients. Additionally, a reliable extraction algorithm is devised to recover the watermark from potentially compromised watermarked images without requiring access to the original image. Through extensive experiments and comparisons with other relevant watermarking algorithms, the findings demonstrate that this scheme effectively embeds a color digital image watermark into the host image. This not only ensures high levels of invisibility but also establishes robustness, making it well-suited for the protection of digital image copyrights.